Placental expression of microRNAs in infants born small for gestational age. (June 2019) - Östling, H.; Kruse, R.; Helenius, G.; Lodefalk, M.
Abstract: Introduction: The molecular mechanisms behind poor foetal growth are not fully known. The aim of this study was to explore global microRNA expression in placentas of infants born small for gestational age (SGA) compared to infants with a normal birth weight (NBW). Methods: Placental biopsies from term infants were identified in a biobank and divided into four groups: infants born SGA with (n = 13) or without (n = 9) exposure to low maternal gestational weight gain (GWG) and infants born with NBWs with (n = 20) or without (n = 26) exposure to low GWG. All women and infants were healthy, and no woman smoked during pregnancy. Only vaginal deliveries were included. Next-generation sequencing was performed with single read sequencing of >9 million reads per sample. Differential microRNA expression was analysed using ANOVA for unequal variances (Welch) with multiple testing corrections through the Benjamini-Hochberg method. A fold change >2 and a corrected p value < 0.05 were considered significant. Adjustments for possible confounding factors were made using a linear regression model. Results: A total of 1870 known, mature human microRNAs were detected in the sample. MiR-3679-5p and miR-193b-3p were significantly upregulated, and miR-379-3p, miR-335-3p, miR-4532, miR-519e-3p, miR-3065-5p, and miR-105-5p were significantly downregulated after adjustment for potential confounding factors in SGA infants with normal GWG compared to infants with NBWs and normal GWG. Discussion: Infants born unexplained SGA show differential microRNA expression in their placenta. Important pathways for the differentially expressed microRNAs include inflammation and the insulin-IGF system. Highlights: Infants born small for gestational age (SGA) express microRNAs in their placentas differently. Two microRNAs were upregulated and six were downregulated in SGA infants. The differentially expressed microRNAs were linked to inflammation. The differentially expressed microRNAs were also linked to the insulin-IGF system. Unexplained SGA births may be caused by subclinical placental inflammation.